A union of peoples - Eleutheriadåes, Paulos Z. (Oxford : Oxford University Press, 2020)
Many political and legal philosophers compare the EU to a federal union. They believe that its basic laws should be subject to the standards of constitutional law. They thus find it lacking or incomplete. This book offers a rival theory. If one looks more closely at the treaties and the precedents of the European courts, one sees that the substance of EU law is international, not constitutional. Just like international law, it applies primarily to the relations between states. It binds domestic institutions directly only when the local constitutions allow it. The member states have democratically chosen to adapt their constitutional arrangements in order to share legislative and executive powers with their partners. The legal architecture of the European Union is thus best understood under a theory of dualism and not pluralism.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 28, 2020).
Keywords: European Union